ANALISIS MINAT BELAJAR SISWA SMP KELAS VIII DI KOTA BANDUNG TERHADAP PEMBELAJARAN MATEMATIKA - Tita Puspita; Indah Retta Fauziah (Departement of Mathematics Education, 2019)
This study aims to analyze how the learning interests of middle school students in the city of Bandung. The learning method used is the method of surveying and interviewing students. The research technique was carried out by distributing learning interest questionnaires which were analyzed descriptively. The questionnaire consists of 12 items with 4 alternative answers namely